Pennington's heir. - Peyton, K. M. (Crowell, 1974)
Traces the early marriage of Pat and Ruth, a young English couple, as Pat endeavors to launch a career as a pianist and forget the nine months he served in prison. Sequel to "The Beethoven Medal."